The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/adfm.201707244
|View full text |Cite
|
Sign up to set email alerts
|

Room‐Temperature Electrochemical Conversion of Metal–Organic Frameworks into Porous Amorphous Metal Sulfides with Tailored Composition and Hydrogen Evolution Activity

Abstract: The conversion of metal-organic frameworks (MOFs) into inorganic nanomaterials is considered as an attractive means to produce highly efficient electrocatalysts for alternative-energy related applications. Yet, traditionally employed MOF-conversion conditions (e.g., pyrolysis) commonly involve multiple complex high-temperature reaction processes, which often make it challenging to control the composition, pore structure, and active-sites of the MOF-derived catalysts. Herein, a general, simple, room-temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
83
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(89 citation statements)
references
References 62 publications
2
83
0
Order By: Relevance
“…The survey spectra of N‐CoS 2 shown in Figure S5 (Supporting Information) further indicates the presence of Co, S, and N. As shown in Figure a, the high‐resolution Co 2p spectra can be divided into Co 2p 3/2 and Co 2p 1/2 . The peaks located at 778.3 and 780.5 eV can be assigned to Co 0 (2p 3/2 ) and Co 2+ (2p 3/2 ), respectively . It can be seen clearly that the peak of Co 0 in N‐CoS 2 displays a positive shift of about 0.05 eV compared to that of CoS 2 .…”
Section: Resultsmentioning
confidence: 90%
“…The survey spectra of N‐CoS 2 shown in Figure S5 (Supporting Information) further indicates the presence of Co, S, and N. As shown in Figure a, the high‐resolution Co 2p spectra can be divided into Co 2p 3/2 and Co 2p 1/2 . The peaks located at 778.3 and 780.5 eV can be assigned to Co 0 (2p 3/2 ) and Co 2+ (2p 3/2 ), respectively . It can be seen clearly that the peak of Co 0 in N‐CoS 2 displays a positive shift of about 0.05 eV compared to that of CoS 2 .…”
Section: Resultsmentioning
confidence: 90%
“…The micropores were beneficial for electrolyte diffusion as well as releasing of hydrogen molecular generated in hydrogen evolution reaction (HER) to reduce the charge/ mass transfer resistance resulting in high electrocatalytic activity, especially under high potential range. [17] Moreover, the EDS mappings depicted that N atoms were homogenously doped into carbon materials and quantitative analysis indicated that N doping amounts were 8.4 at%, 11.0 at%, 20.1 at% and 24.7 at% for PNC-1, PNC-2, PNC-3 and PNC-4, respectively. Continuously, the specific surface areas of different electrocatalysts were measured and shown in Figure S2a, in which the specific surface areas of PNC-0, PNC-1, PNC-2, PNC-3 and PNC-4 were 1156, 1075, 979, 850 and 1074 m 2 g À1 , respectively.…”
Section: Resultsmentioning
confidence: 97%
“…The better catalytic performance of porous CoP concave polyhedron should be associated with the porous structure, large surface area and highly conductive carbon network. Hod's group developed a facile experimental method to synthesize porous amorphous CoS x by the electrochemical conversion of ZIF‐67 MOF with various potential scan rates during the CV‐cycling . As shown in Figure e and f, the as‐prepared CoS x ‐(0.2–0.02)‐12, obtained after an electrochemical conversion of ZIF‐67 (12 growth cycles) with altered scan rates from 0.2 to 0.02 V s −1 , the overpotential of 168 mV at 10 mA cm −2 in neutral pH.…”
Section: Design Of Mof‐based Materials With High Activity Towards Watmentioning
confidence: 99%
“…e) Schematic illustration showing the electrochemical conversion of ZIF‐67 to porous amorphous CoS x and f) the corresponding voltammetric curves and Tafel plots for the amorphous CoS x compared with other related catalysts. Reproduced with permission from reference . Copyright 2018, Wiley‐VCH.…”
Section: Design Of Mof‐based Materials With High Activity Towards Watmentioning
confidence: 99%